Gender, Ethnicity, and Education–Job Mismatch in Afghanistan: Evidence from Kabul University Graduates - Mohammad Samim Miskinyar; Shuaib Hakimi; Musawer Hakimi (Universitas Pendidikan Nasional, 2026)
The objective of this paper is to examine the impact of gender and ethnicity on the incidence of education job-mismatch among graduates of Kabul University. Using data collected from 272 graduates of Kabul University’s 2015 cohort and employing a logistic regression model, this study investigates whether the Afghan labor market provides equal opportunities for these graduates to obtain jobs related to their fields of study, regardless of their gender and ethnic background. More than half of the graduates (55.5%) are employed in jobs that do not match their academic disciplines. However, gender and ethnicity do not play a statistically significant role in this mismatch. This investigation was limited to a specific population, namely, graduates of Kabul University in 2015. Despite broader gender and ethnic inequalities in Afghan society, this study suggests that the country’s labor market offers relatively equal opportunities for graduates to find appropriate employment. - This pattern of equality in Afghanistan’s labor market should be strengthened and sustained through regular, broader assessments and the implementation of practical steps.